Application of Edible Vaccines: Penerapan Vaksin yang Dapat Dimakan - Mahmood, Huda M.; Hmood, Tabark Sh.; Dhaip, Nuha A.; Mikhlif, Maymouna Y.; Majeed, Sadin R.; Faydh, Donia S. (Indonesian Journal on Health Science and Medicine, 2025)
Immunizing humans and animals with edible plants is a developing technique with It appears limitless possibilities. The selected/desired pathogen antigen (HIV, TB, etc.) is injected via the chosen the host plant via the changes procedure as an create a plant that has been altered. Vegetable vaccinations have a lot of potential as a profitable, easy-to-manage, conveniently stored, unlikely or incapable of failure, and sociocultural sustainable option, especially for poor emerging economies. An edible vaccination replaces sore immunization protocols. Compared to conventional vaccines, edible vaccines are less expensive, without needles eliminate the actual need in order to preserve, are safe, might be kept in storage close as an the point of the use, along with provide mucosal layer and whole protection. To enhance human and animal immunity against a variety In viral illnesses, the chosen or preferred antigens The chosen host plant is infected with a variety of viruses, including HIV, TB, etc. There are several different kinds of edible vaccinations under development. to enhance immunity in both people and animals to a variety of infectious illnesses, including hepatitis B, cholera, measles, and FMD. Edible vaccinations can also aid in overcoming autoimmunity illnesses like type 1 diabetes. Edible vaccines have the dual benefit of immunizing generations while also preventing hunger. If the major issues and challenges can be overcome, it will pave the way for more secure and effective immunization Highlights: Edible vaccines: Cost-effective, needle-free, and easily stored for immunization. Targets diseases: HIV, TB, hepatitis B, cholera, measles, FMD, and more. Potential benefits: Enhances immunity, prevents hunger, and supports global health. Keywords: Plant-derived vaccines, immunization, future prospective